The DREAMS Team: Creating community partnerships through research advocacy training for diverse older adults. Issue 9 (2nd September 2017) - Hart, Ariel R.; Dillard, Rebecca; Perkins, Molly M.; Vaughan, Camille P.; Kinlaw, Kathy; McKay, J. Lucas; Waldrop-Valverde, Drenna; Hagen, Kimberley; Wincek, Ron C.; Hackney, Madeleine E.
ABSTRACT: The DREAMS Team research advocacy training program helps clinical faculty and health students introduce basic clinical research concepts to diverse older adults to galvanize their active involvement in the research process. Older adults are frequently underrepresented in clinical research, due to barriers to participation including distrust, historical mistreatment, and their lack of health literacy. The DREAMS Team program aims to involve diverse older adults throughout all phases of research and increase research participation, thereby contributing to the growth of quality patient-centered, evidence-based health care. This course was developed for clinical faculty to deliver to diverse adults aged 55+ in eight 50-minute lectures, followed by half-hour small group discussions moderated by health students. A pilot cohort of 24 individuals was assessed for satisfaction post-program, and self-efficacy before and after the program. Older adult participants improved on a survey measure of self-efficacy, and indicated satisfaction on a post-program questionnaire. All agreed or strongly agreed that they enjoyed participating, and that classes enhanced knowledge/skills about the topics, were high quality, and provided useful information. Twenty-two out of 24 individuals who completed the program indicated they planned to get involved as research advocates. The DREAMS Team program can be offered either on its own, or as a follow-up program to a general health education course led by health students and/or professional researchers or clinicians. Educating older adults about the research process and advocacy through interactive seminars led by congenial and respectful researchers and health students may remove some barriers to research participation and involvement among diverse older adults.